COVID-19 Vaccination during Pregnancy in Southeast Asia - Jia Ni Kwan; Hong Chuan Loh; Irene Looi (Progress in Microbes and Molecular Biology)
Southeast Asia is rapidly becoming the region hit hardest by coronavirus disease (COVID-19), as evidenced by the surging daily number of new confirmed cases and deaths. The COVID-19 crisis continues to worsen with the entry of the more transmissible variants of concern, primarily the Delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which was first identified in India. Pregnant women are among the vulnerable population groups at risk of suffering from severe COVID-19 and may experience poor pregnancy and neonatal outcomes due to the infection. Vaccination seems to be the most effective strategy to curb the pandemic and secondarily by social distancing, wearing face masks and practising hand hygiene. There has been limited yet reassuring evidence in support of vaccinating pregnant women against COVID-19. We sought to review the latest evidence regarding the safety, immunogenicity and reactogenicity of COVID-19 vaccines in pregnant women as well as the recommendations and guidance provided by the public health authorities in the countries in Southeast Asia.